PERANAN PERTAPAAN TRAPPIST SANTA MARIA RAWASENENG TERHADAP PENINGKATAN KESEJAHTERAAN SOSIAL EKONOMI MASYARAKAT DESA NGEMPALAK DAN SEKITARNYA - Sr. Margarethe (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
This paper is based on the author's study on trappist Monks Santa Maria participation in increasing social and economic condition the community of Ngemplak village and its surrounding carried out in August-until October 1995. The results shows that the Monks is very contributive in increasing both social and economic condition of the community by giving aid for field work in term of education (formal and non-formal), health, and business. This attitude, therefore need to be apply by others monks in Indonesia.